Analysis of Interactions between the Epidermal Growth Factor Receptor and Soluble Ligands on the Basis of Single‐Molecule Diffusivity in the Membrane of Living Cells1. (4th May 2015) - Kim, Do‐Hyeon; Zhou, Kai; Kim, Dong‐Kyun; Park, Soyeon; Noh, Jungeun; Kwon, Yonghoon; Kim, Dayea; Song, Nam Woong; Lee, Jong‐Bong; Suh, Pann‐Ghill; Lee, Nam Ki; Ryu, Sung Ho
Abstract We present a single‐molecule diffusional‐mobility‐shift assay (smDIMSA) for analyzing the interactions between membrane and water‐soluble proteins in the crowded membrane of living cells. We found that ligand–receptor interactions decreased the diffusional mobility of ErbB receptors and β‐adrenergic receptors, as determined by single‐particle tracking with super‐resolution microscopy. The shift in diffusional mobility was sensitive to the size of the water‐soluble binders that ranged from a few tens of kilodaltons to several hundred kilodaltons. This technique was used to quantitatively analyze the dissociation constant and the cooperativity of antibody interactions with the epidermal growth factor receptor and its mutants. smDIMSA enables the quantitative investigation of previously undetected ligand–receptor interactions in the intact membrane of living cells on the basis of the diffusivity of single‐molecule membrane proteins without ligand labeling.